Balancing hope with reality: how neonatal nurses manage the uncertainty of caring for extremely premature babies. Issue 17 (4th March 2015) - Green, Janet; Darbyshire, Philip; Adams, Anne; Jackson, Debra
<x xml:space="preserve">Abstract</x> Aims and objectives This article aims to explore the ways in which neonatal nurses manage the uncertainty associated with the treatment and outcomes of extremely premature babies. Background Current literature suggests that survival rates of extremely premature babies have increased; however, the incidence of long‐term problems has not decreased among survivors. The outcomes can often not be predicted; therefore, there is much uncertainty associated with survival and outcomes. Neonatal nurses care for babies and families during these times of uncertainty. This article will focus on how neonatal nurses manage and survive the challenges associated with uncertainty when caring for extremely premature babies. Design Qualitative. Methods This article used a series of interviews in a qualitative study informed by phenomenological insights. The analysis of the interview data involved the discovery of thematic statements and the analysis of the emerging themes. Results Three themes captured the experience of working with uncertainty from the perspective of the neonatal nurses: 'Everything is fine, then they crash': When the honeymoon is over; '"I don't know which one is going to be fine": it's like a lottery' and 'Balancing hope with reality'. Conclusion Uncertainty had both positive and negative aspects, because while ever there was uncertainty, there was room for hope. While initial uncertainty of the baby's prognosis and outcome gave the nurses hope, certainty of diagnosis and poor outcome could take that hope away. Relevance to clinical practice Increasing survival of extremely premature babies will see neonatal nurses caring for more babies ≤24 weeks gestation. Prematurity has risks associated with life‐sustaining treatments. Uncertainty is a reality of life for these babies, their families and the nursing and medical teams who care for them. It is important to recognise the challenges associated with uncertainty.